Literature review of the portrayal of dentists and teeth in movies - Yeung, Andy Wai Kan (Frontiers in Oral Health, 2025)
IntroductionThere are multiple portrayals of dentists and teeth in movies. It is largely unclear if the literature has investigated these portrayals. This literature review aimed to identify and analyze the themes, narratives, and symbolic meanings associated with dental portrayal in movies from the existing literature.MethodsOnline literature databases, Web of Science, Scopus, and PubMed, were searched to identify relevant papers labelled as articles or reviews. Publications were included if they described or investigated the portrayal of dentists or teeth in multiple commercial movies. Publications were excluded if they were irrelevant to this topic or provided commentary on a single movie only. Finally, 7 publications were identified and reviewed. For each publication, its study design, data source, and genres of movies analyzed were recorded. Key findings were reviewed, such as themes or stereotypes identified, positive vs. negative portrayals, and any impact on public perception elaborated.ResultsThese papers were published between 2007 and 2024. Five of them provided qualitative content analysis, whereas 2 provided quantitative content analysis. Three publications consulted Internet Movie Database (IMDb) to identify relevant movies. Many of the publications did not explicitly report very detailed inclusion and exclusion criteria for the selection of movies. The portrayal of dentists was covered in 5 publications. The symbolic meaning of teeth was covered in 2 publications. (One publication covered both dentist portrayal and teeth symbolism.) Scenes of oral hygiene practice were investigated in 1 publication.ConclusionThe portrayal of dentists in movies has often been negative, which may influence public perception and contribute to dental anxiety. Future research should investigate the impact of these portrayals on audience attitudes and behavior, as this review underscores the need for more empirical studies in this area. Meanwhile, readers should notice that one major limitation of this review is the small number of publications included.